Socialization of Ecotourism Improvement Strategy in Teratak Village - Uyun, Musmiratul; Puspita, Baiq Hasta; Wibisana, Gunawan; Alpiransyah, Alpiransyah; Maulana, Andrian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Ecotourism is a form of tourism that focuses on the sustainability of the natural environment and the active participation of local communities in the management and development of tourist destinations. Teratak Village, as one of the areas rich in natural and cultural potential, has the opportunity to develop the ecotourism sector to improve community welfare while preserving the environment. This research aims to explain the process of socialization of ecotourism improvement strategies in Teratak Village. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and analysis of related documents. The results showed that the socialization of ecotourism improvement strategies in Teratak Village involved collaborative steps between the village government, local communities, and related parties. The socialization process begins with the identification of the potential of natural, cultural, and human resources that can be integrated into ecotourism products. Next, through participatory meetings and workshops, a sustainable ecotourism development strategy was formulated. Socialization is followed by communicating this strategy to the entire community through public meetings, local media, and environmental awareness campaigns. In the socialization process, the importance of active community involvement in the management of ecotourism destinations was emphasized. Education on the importance of environmental preservation and sustainable.